Clinical presentations of substance abuse in bipolar heroin addicts at time of treatment entry - Maremmani, Icro (BioMed Central, 2012)
BACKGROUND: Studies on the ‘self-medication hypothesis’ have focused on substance abuse as an attempt to alleviate emotional suffering. METHODS: We have investigated concomitant substances of abuse in 150 bipolar heroin addicts clustered according to their clinical presentation at treatment entry (depressive episode, hypomanic episode, manic episode and mixed episode). Bipolar heroin addicted patients were chosen because they tend to have a concomitant poly-substance abuse and because, as compared with patients suffering for other mental illnesses, they more clearly reveal a variety of identifiable affective states. RESULTS: Patients with a depressive episode more frequently used non-prescribed anxiolytic-hypnotics. They were found to use cocaine-amphetamines more frequently during a hypomanic episode, whereas the use of cannabis and cocaine-amphetamines occurred more frequently during a manic episode. The associated use of alcohol, cocaine-amphetamines and cannabinoids was more frequently encountered during a mixed episode. Limitations: apart from the difficulty in determining whether the substance use modifies the mood or the mood state determines the substance used, this is a report on a retrospective analysis, rather than a study specifically designed to elucidate the issue; in addition, no information was available on the temperament of our subjects. Assessments of the same subject in various clinical presentations would have provided a better level of information. CONCLUSIONS: Besides one expected result – the prominent use of CNS stimulants during a depressive phase of bipolar patients – this study supports the hypothesis that mood elation is a pleasurable, rewarding experience that, in bipolar patients, can be started or prolonged by means of CNS stimulant drugs. Stimulant use was, therefore, more prevalent during the ‘up’ rather than the ‘down’ phase of the illness.